An updated taxonomic circumscription of Tricholoma mesoamericanum that includes Tricholoma colposii (Agaricales, Tricholomataceae) - Bandala, Víctor M.; Ramos, Antero; César, Enrique; Ramos, David; Montoya Bello, Leticia (Instituto de Ecología, A.C., 2022)
Background and Aims: The species recorded in Mexico (state of Veracruz) in the 1980s as “Tricholoma magnivelare” (or under its synonym, T. ponderosum) changed over the years from being a fungus not considered to be edible in this country, to a subject of international commercialization when Asian sellers became aware of its occurrence in Mexico and for its relationship with the group of T. matsutake. The collections supporting these previous records from different regions of the country (and identified under the same name) were studied only morphologically. Based on morphological and molecular information (ITS), T. mesoamericanum was described from Oaxaca state (southern Mexico) (type), while T. colposii was more recently described from Veracruz state, both related to the group of species around T. matsutake. The aim of this study was to determine, with morphological characters and sequences (ITS) obtained from fresh samples, the taxonomic identity of specimens morphologically resembling those species.Methods: Field work was carried out during 2009 and 2018 in two Pinus-forested sites in the states of Puebla and Veracruz (eastern Mexico). Fruit bodies acquired in a popular market in the city of Xalapa, Veracruz, were also studied. Measurements, color and the morpho-anatomical and organoleptic characteristics of the samples were recorded. DNA extraction, PCR, sequencing of the Internal Transcribed Spacer (ITS) region of ribosomal DNA, and a phylogenetic analysis were conducted.Key results: Molecular and morphological studies presented here reveal that Mexican populations of “T. magnivelare” sampled in the states of Veracruz and Puebla are grouped in a clade including T. mesoamericanum and T. colposii type specimens, separate from T. magnivelare s. str. from USA. Conclusions: The identity of the material studied corresponds to T. mesoamericanum, which is consistent with previous studies showing that the “matsutake” mushrooms in the country represent T. mesoamericanum, and as shown here, with T. colposii as a synonym.